NATIONAL DYNAMICS OF YOUTH OF 1950-1960 GENERATION AS A WAY OF TRANSFORMING THE SOCIETY IN J. D. SALINGER’S ‘THE CATCHER IN THE RYE’ AND ‘YOUTH PROSE’ OF VASILY AKSYONOV EXEMPLIFIED BY ‘TICKET TO THE STARS’ NOVEL (Revista Inclusiones, 2020)
The relevance of the presented research is due to the call to determine the reference points of cultural interaction between Russian and American literature of the 20th century in the context of the nationwide dynamics of the young generation of the 1950-1960s, reflected in the novel by the American classic J. Salinger ‘The Catcher in the Rye’ and the youth prose of the Russian writer in exile Vasily Aksyonov. In this context, the purpose of this article is to disclose the influence of American literature on the development of the young generation of Russian writers, reflecting significant cultural changes in Soviet society on the example of Salinger’s and Aksyonov’s creative interlocution. The leading method in the study of this problem is the imagological approach. This methodallows comprehensively considering American and Russian literature as imagological systems revealing the characteristics of national ethnotypes and their interaction with foreign cultures. Imagology, as a scientific method of this article, expands the possibilities of a comparative historical and descriptive approach exploring the general typological aspects of a literary phenomenon. As a study material, the novels by J. Salinger ‘The Catcher in the Rye’ and V. Aksyonov ‘Ticket to the Stars’ are considered as imagological systems reflecting the peculiarities of the sociocultural and national dynamics of the young generation of the 1950s and 1960s in the broad context of world literature.